Os caminhos da educação integral em Palmas-Tocantins - Alves, Roneidi Pereira de Sá (2013)
This study integrates the line of research entitled "State and Education Policy" of the Graduate Education, of the Faculty of Education, at the Federal University of Goiás. The aim of this research was to analyse the experience of full-time education, in the Municipal Education System, in Palmas, from 2005 to 2011. It was chosen to adopt two instruments: a bibliographical and documentary research, to identify and analyse the reflections already elaborated on Full-time Education. It is Integrated in the list of documents of this research: the proposal of the implementation of the full-time schooling in the Northern Region of the Municipal Education System of Palmas; official reports; architectural projects of the schools surveyed, payroll and modular structure of the school. It is considered as the base of information the official documents such as laws, ordinances, decrees, resolutions and opinions. In this experiment, the term holistic education refers to the extension of time and space for students remaining in school, diversification of activities and pedagogical actions, aiming to meet the diverse areas of human knowledge and the reorganisation of the curriculum in accordance with the point of view of the following authors, such as Rabbit; Cavaliere (2002), Guara (2010) and Moreira (2006). This proposal was conceived as a possibility to achieve a better quality of education, providing more time to the students in the schools. It is noticed the existence of suitable and inadequate space to offer a full-time study, which is the indicative of 40 hours, in one school. It appears, though, the cost of student charged in Palmas-year - is higher than the percentage set by Fundeb for the state of Tocantins. Finally, it is highlighted the need for a better understanding of public finance and municipal transparency of use of resource, enabling analysis resulting from research as they offered to do.